Pengaruh Penggunaan Aplikasi SiKadir (Absensi Digital) dan Pengawasan Kerja terhadap Kinerja Pegawai Manggala Agni Daops Sumatera XVI/Lahat - Hayani; Fytaloka, Vemi; Suryanti, Lilis; Iskandar; Agel Al Haffizh Ramadhan, Muhammad (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2025)
This study aims to analyze the influence of the SiKadir application (digital attendance) and work supervision on employee performance at Manggala Agni Daops Sumatera XVI/Lahat. The research employed a quantitative approach with a census method involving 60 respondents. Data were analyzed using multiple linear regression with SPSS software. The findings reveal that both the SiKadir application and work supervision have a positive and significant effect, individually and simultaneously, on employee performance. The adjusted R² value of 0.892 indicates that the independent variables explain 89.2% of the variation in employee performance. Keywords : SiKadir Application (Digital Attendance), work supervision, employee performance